Пошаговое объяснение:
Xo= -b/2a, Yo=y(Xo)=...
a) Xo=-4/2=-2 Yo=Y(-2)=(-2)^2 +4*(-2) +3= 4-8+3=-1 отв. (-2;-1)
б) Xo=-16/2*2=-4 Yo=Y(-4) =2*16+16*(-4)) +72=32-64+72=40, отв. (-4;40)
f) Xo=-24/-12=2, Yo=Y(2)= -6*4+24*2+24=48, отв (2;48)
остальные также
Пошаговое объяснение:
Xo= -b/2a, Yo=y(Xo)=...
a) Xo=-4/2=-2 Yo=Y(-2)=(-2)^2 +4*(-2) +3= 4-8+3=-1 отв. (-2;-1)
б) Xo=-16/2*2=-4 Yo=Y(-4) =2*16+16*(-4)) +72=32-64+72=40, отв. (-4;40)
f) Xo=-24/-12=2, Yo=Y(2)= -6*4+24*2+24=48, отв (2;48)
остальные также